New caryophyllene-type sesquiterpene and flavonol tetraglycoside with sixteen known compounds from sword bean (Canavalia gladiata) - An, Hyun Jeong; Kim, Eun Hee; Lee, Hyoung Jae; Cho, Jeong-Yong; Moon, Jae-Hak (Food science and biotechnology, 2020)
Eighteen compounds including new caryophyllene-type sesquiterpene and flavonol tetraglycoside were purified and isolated from sword beans ( Canavalia gladiata ). Two new compounds, ( Z ,1 R ,7 S ,9 S )-7-hydroxy-11,11-dimethyl-8-methylenebicyclo[7.2.0]undec-4-ene-4-carboxylic acid ( 2 ) and kaempferol-7- O -α- l -dirhamnopyranosyl(1 → 2;1 → 6)- O -β- d -glucopyranosyl(1 → 2)- O -α- l -rhamnopyranoside ( 9 ), were identified. Other known compounds including methyl gallate ( 1 ), (2 S ,3 S ,4 E ,8 E )-2-aminooctadeca-4,8-diene-1,3-diol 1- O -β- d -glucopyranoside ( 3 ), (2 S ,3 S ,4 E ,8 Z )-2-aminooctadeca-4,8-diene-1,3-diol 1- O -β- d -glucopyranoside ( 4 ), lupeol ( 5 ), trilinolein ( 6 ), 1,6-di- O -galloyl β- d -glucopyranoside ( 7 ), N -(2-methoxybenzoyl)homoserine ( 8 ), dihydrophaseic acid ( 10 ), dillenetin ( 11 ), kaempferol-7- O -[2- O -β- d -glucopyranosyl-6- O -α- l -rhamnopyranosyl]-α- l -rhamnopyranoside ( 12 ), canavalioside ( 13 ), kaempferol-3- O -[2- O -β- d -glucopyranosyl-6- O -α- l -rhamnopyranosyl]-β- d -glucopyranoside ( 14 ), kaempferol-3- O -(2,6- O -α- l -dirhamnopyranosyl)-β- d -glucopyranoside ( 15 ), kaempferol-3- O -rutinoside ( 16 ), gladiatoside A 1 ( 17 ), and gladiatoside B 1 ( 18 ) were identified. The chemical structures of these compounds were determined by ESI–MS and NMR analyses.